Yolk sac tumor of the vulva: A case report with long-term disease-free survival - Khunamornpong S. (2014)
Background. Yolk sac tumor (YST) of the vulva is extremely rare. Seven cases of vulvar YST have been reported to the literature. Due to the rarity of tumors, the appropriate choice of treatment may remain unclear. Case. A 30-year-old woman presented with a 3.5-cm right labial mass. Excisional biopsy showed YST with predominant solid pattern. Three weeks after excision, right inguinal lymph node biopsy revealed metastatic tumor. The serum alpha-fetoprotein (AFP) was not elevated. Cisplatin-based chemotherapy was administered, followed by pelvic and groin irradiation. The patient was free of disease 90 months after the diagnosis. Conclusion. Local excision of tumor with adjuvant cisplatin-based chemotherapy can be justified for vulvar YST. Inguinal lymphadenectomy is recommended because metastasis may occur early. Adjuvant radiation therapy may help to control the disease. Tumor size of 5 cm or less may be a favorable prognostic factor. Serum AFP level may not be a sensitive marker for follow-up of vulvar YST. © 2005 Elsevier Inc. All rights reserved.